Analysis of the Sensory Attribute Profile of Kupang Crackers Produced by MSMEs in Candi District, Sidoarjo Regency Using the Rate-All-That-Apply (RATA) Method - Atzmarany Putri Arprassinta; Ulya Sarofa; Luqman Agung Wicaksono (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Kupang crackers are a traditional processed food product from Sidoarjo Regency that exhibit diverse sensory characteristics due to differences in raw materials and processing methods among MSMEs. This study aims to identify the sensory attribute profiles of kupang crackers produced by MSMEs in Candi District, Sidoarjo Regency using the Rate-All-That-Apply (RATA) method, analyze the relationships among sensory attributes using Principal Component Analysis (PCA), and evaluate consumer preference levels through hedonic testing and preference mapping. The study utilized seven samples of kupang crackers selected through purposive sampling from different SMEs in Candi Subdistrict and involved 100 consumer panelists’. RATA and hedonic data were analyzed using the Kruskal-Wallis test and Dunn's post-hoc test, while. PCA and preference mapping were used to fillustrate the relationship between sensory characteristics and consumer preferences using XLSTAT 2019. The results showed that most sensory attributes differed significantly across samples, except for umami aroma, saltiness, and umami taste. PCA explained 69.26% of the variance in the sensory data and indicated differences in sensory characteristics among the samples. Overall, the hedonic test results indicated differences in consumer liking levels, while preference mapping showed that the characteristics of white color, sweet taste, and crispy texture tended to be associated with higher consumer preferences. Conversely, fatty, oily, rough, and gritty attributes tended to fall within regions of lower preference. The research results can serve as a basis for MSMEs to evaluate and develop the sensory characteristics of kupang crackers in accordance with consumer preferences. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 12: Responsible, Consumption, and ProductionSDG 2: Zero Hunger